Environmental Sustainability: Clay Solution to High Cost of Building Materials in Construction Industry (British Journal of Multidisciplinary and Advanced Studies, 2022)
The objective of this paper is to identify the social, economic and environmental sustainable significant of clay as a building material in the construction industry. Building materials are considered the largest input in any building project therefore, has a great influence on the total cost of any projects. High cost of projects calls for in co-opting clay products in most past and present building projects. The research is aimed to identify significant of clay as solution to high cost of building materials in the construction industry. The research was carried out in suitable civil and building construction companies in Katsina, Kano and Kaduna states in Northern Nigeria. The research findings reveled that economic factors has the highest significant as sustainable building materials in the construction industry.
Keywords: Building Industry; Building Materials; Clay; Economic; Environmental; High Cost